Globotics and development: When manufacturing is jobless and services are tradable - Richard E. Baldwin; Rikard Forslid (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Globalization and robotics (globotics) are transforming the world economy at an explosive pace since they are driven by digital technology that is advancing in phenomenal increments. This paper - which should be considered a 'thought piece' - argues that the globotics transformation is likely to disable the traditional manufacturing-led development 'journey' of the type China is taking, while enabling the service-led development journey of the type India is following. We start with a historical perspective on the current transformation before turning to a consideration of the technology and a closer look at the economic logic that is making manufacturing jobless and services traded. Finally, we discuss how one might conceptualize service-led development.
Keywords: F10; F14; O10; O14; 330; globalization; robotics; service-led development